Lightweight Time Warp- A Novel Protocol for Parallel Optimistic Simulation of Large-Scale DEVS and Cell-DEVS Models - Qi Liu; Wainer, G. (2008 12th IEEE/ACM International Symposium on Distributed Simulation and Real-Time Applications, 2008)
This paper proposes a novel lightweight time warp (LTW) protocol for high-performance parallel optimistic simulation of large-scale DEVS and cell-DEVS models. By exploiting the characteristics of the simulation process, the protocol is able to set free most logical processes (LPs) from the time warp mechanism, while the overall simulation still executes optimistically, driven by only a few full-fledged time warp LPs. The LTW protocol includes a rule-based event-scheduling mechanism using two types of event queues, an aggregated state-saving technique for optimal risk-free state management, and a new rollback algorithm that recovers lightweight LPs from causality errors without sending anti-messages. The impact on global control mechanisms such as GVT computation, fossil collection, and load migration is also discussed. The basic concepts of the protocol could also apply to a broad range of time warp systems under certain conditions and with appropriate control over the LPs.